Opiate Drugs with Abuse Liability Hijack the Endogenous Opioid System to Disrupt Neuronal and Glial Maturation in the Central Nervous System - Hauser, Kurt F.; Knapp, Pamela E. (Frontiers in Pediatrics, 2018)
The endogenous opioid system, which is comprised of multiple opioid neuropeptide and receptor gene families, is highly expressed by developing neural cells and can significantly influence neuronal and glial maturation. In many central nervous system (CNS) regions, the expression of opioid peptides and receptors occurs only transiently during development, effectively disappearing with subsequent maturation only to reemerge under pathologic conditions, such as with inflammation or injury. Opiate drugs with abuse liability act to modify growth and development by mimicking the actions of endogenous opioids. Although typically mediated by the µ-opioid receptors, stimulating both δ- and κ- opioid receptors can also modulate growth in a cell-type, region-specific, and developmentally regulated manner. Thus, opioids act as biological response modifiers and their actions are highly contextual, plastic, modifiable, and influenced by other physiological processes or pathophysiological conditions such as neuro-acquired immunodeficiency syndrome. To date, most studies have considered the acute effects of opiates on cellular maturation. For example, activating opioid receptors typically results in acute growth inhibition in both neurons and glia. However, with sustained opioid exposure, compensatory factors become operative, a concept that has been largely overlooked during CNS maturation. Accordingly, this review surveys prior studies on the effects of opiates on CNS maturation, and also suggests new directions for future research in this area. Identifying the cellular and molecular mechanisms underlying the adaptive responses to chronic opiate exposure (e.g., tolerance) during maturation is crucial toward understanding the consequences of perinatal opiate exposure on the CNS.